RELATION BETWEEN STATE-TEST ANXIETY AND EXAM PERFORMANCE IN COLLEGE STUDENTS: PRELIMINARY ANALYSIS OF THE DIFFERENCE AS PER COURSE - Dominguez-Lara, Sergio Alexis (2017)
The objective of this study was to find out if the relation between State - Test Anxiety (S-TA) and Exam Performance (EP) varies between two groups of students from different terms. The study was conducted on 76 Psychology program students (87.1 % female) in the fourth term (n = 44), and the seventh term (n = 32), from a private university located in Lima Metropolitan Area, between the ages of 18 and 30 (M = 22.07). The State Test - Anxiety Inventory (S-TAI) and two brief measures—academic self-efficacy and academic emotional exhaustion—were applied. The relation found between S-TA and EP was negative and significant, but of different magnitude according to the academic term. The implications of the study are discussed.